Enhancing patient care: Ethical considerations for micronutrient management in hospital nutrition settings - Dian Permatasari (Indonesian Nutrition Association, 2023)
Micronutrients are represented by vitamins and minerals and are present in a wide variety of foods. Each of these nutrients performs specific functions that are essential for the health of our cells and their harmonious functioning. Data suggest that many people have an inadequate daily intake of micronutrients, even when nutritious food is more easily available. It has since been established that the complex, integrated immune system needs multiple specific micronutrients, including vitamins A, D, C, E, B6, and B12, folate, zinc, iron, copper, and selenium, which play vital, often synergistic roles at every stage of the immune response.